The fantasy of female sexual freedom in Angela Carter's The Bloody Chamber and in John Logan's Penny Dreadful. - Bernhardt, Lara Catherine (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.